Validity of a Kahoot!-Based Cognitive Test Instrument on Corona Pandemic Theme - Taufik, Annisa Novianti; Berlian, Liska; Suryani, Dwi Indah; Nulhakim, Lukman; Rohimah, Rt. Bai; Ansori, Muhammad (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2021)
This study aimed to determine the level of expert validation of a developed Kahoot!-based cognitive test instrument on corona pandemic theme in the Integrated Science course. The research used the Research and Development (R&D) 3D model. The assessment instrument was developed on a web basis using the Kahoot! platform. The data were analyzed by quantitative and qualitative descriptive analysis based on the validity of the questions obtained through expert validation tests. The results showed that the cognitive test instrument developed obtained an average score of 4.57 with a very valid category referring to the distribution of the three aspects of the assessment, where the construction and material aspects are in the very valid category, and the language aspect is included in the valid category. It can be concluded that the instrument made are in accordance with the standards and assessment criteria. So, developed Kahoot!-based cognitive test instrument can be used to assess cognitive aspect of pre-service science teacher on Corona Pandemic Theme.